2020
DOI: 10.3390/ma13225073
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Solvent on the Crystal Packing of Ethacridinium Phthalate Solvates

Abstract: The synthesis, structural characterization and influence of solvents on the crystal packing of solvated complexes of ethacridine with phthalic acid: 6,9-diamino-2-ethoxyacridinium phthalate methanol solvate (1), 6,9-diamino-2-ethoxyacridinium phthalate ethanol solvate (2), 6,9-diamino-2-ethoxyacridinium phthalate isobutanol solvate (3), and 6,9-diamino-2-ethoxyacridinium phthalate tert-butanol solvate monohydrate (4) are described in this article. Single-crystal XRD measurements revealed that the compounds 1–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The similar heterohexamer we observed in the crystal structures of ethacridinium phthalate isobutanol solvate [66], where instead of the ethanol molecule there is an isobutanol molecule, but the distance between mean planes of ethacridinium is longer in the crystal of compound 2 (3.431 Å and 3.545 Å in the crystal of ethacridinium phthalate isobutanol solvate and compound 2, respectively). In the crystal structure of compound 2, neighboring heterohexamers are linked via π-π interactions and π-stacked columns of ethacridine are formed, whereas inversely oriented diclofenac anions interact through π-π interactions each other and linked these columns.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The similar heterohexamer we observed in the crystal structures of ethacridinium phthalate isobutanol solvate [66], where instead of the ethanol molecule there is an isobutanol molecule, but the distance between mean planes of ethacridinium is longer in the crystal of compound 2 (3.431 Å and 3.545 Å in the crystal of ethacridinium phthalate isobutanol solvate and compound 2, respectively). In the crystal structure of compound 2, neighboring heterohexamers are linked via π-π interactions and π-stacked columns of ethacridine are formed, whereas inversely oriented diclofenac anions interact through π-π interactions each other and linked these columns.…”
Section: Discussionsupporting
confidence: 79%
“…This is due to fact that acridines can intercalate into DNA which makes them exhibit anticancer, antibacterial, antiprion, and antiviral effects, among others [58][59][60][61][62]. Our previous research shows that acridine and its derivatives may interact with coformer molecules through various intermolecular interactions, such as hydrogen bonds, halogen bonds, π-π stacking interactions, and are able to form good quality crystals that are stable at room temperature [63][64][65][66]. One of the acridine derivatives represent interesting medicinal activity is ethacridine.…”
Section: Introductionmentioning
confidence: 99%
“…The employment of different crystallization solvents can produce indeed different crystal forms, where the solvent molecules could affect the solid state assembly [4,5]. The effect of the solvent can indeed influence the growth, the morphology and the packing of crystal structures [6][7][8][9][10][11][12][13][14], so that the same ligand can crystallize in different forms [4].…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Recently we have presented results regarding the capabilities of different solvents to induce cocrystallization in acridine-based molecular crystals of APIs. 30 Some of us demonstrated that, in similar cases, cocrystallization 31 and solid-state reactions 32 can be carried out directly in the solid state under dry conditions with high conversion rates and with the additional advantage of eliminating solvents. 33 In this work, the cocrystallization of naproxen with some acridines is thus attempted by three different approaches: (i) solution methods, (ii) liquid-assisted grinding (LAG), and (iii) solidstate thermal approach, heating the sample just below or above the melting point of the reactants to explore the molecular landscape of the target compounds.…”
Section: Introductionmentioning
confidence: 99%